1962
DOI: 10.1128/jb.83.6.1274-1280.1962
|View full text |Cite
|
Sign up to set email alerts
|

RAPID LETHAL EFFECT IN RATS OF A THIRD COMPONENT FOUND UPON FRACTIONATING THE TOXIN OF BACILLUS ANTHRACIS

Abstract: BEALL, FRANCIS A. (U.S. Army Chemical Corps, Frederick, Md.), MARTHA J. TAYLOR, AND CURTIS B. THORNE. Rapid lethal effect in rats of a third component found upon fractionating the toxin of Bacillus anthracis. J. Bacteriol. 83:1274-1280. 1962.-Rats were found to be more susceptible to the lethal effect of toxin produced by Bacillus anthracis in vitro than were several species considered less resistant to anthrax. Rats were killed much faster by less toxin per gram of body weight than were mice. Guinea pigs surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(76 citation statements)
references
References 6 publications
0
72
1
2
Order By: Relevance
“…toxicity (Beall et al, 1962;Haines et al, 1965). Studies have suggested that LeTx induces hypotensive shock in rats by depressing cardiac ventricular activity (Watson et al, 2007;Kuo et al, 2008).…”
Section: Immunology and Medical Microbiologymentioning
confidence: 99%
“…toxicity (Beall et al, 1962;Haines et al, 1965). Studies have suggested that LeTx induces hypotensive shock in rats by depressing cardiac ventricular activity (Watson et al, 2007;Kuo et al, 2008).…”
Section: Immunology and Medical Microbiologymentioning
confidence: 99%
“…These three factors are the protective antigen (PA), the lethal factor (LF) and the oedema factor (EF). Intravenous injections of PA + LF (lethal toxin, LT) have been shown to be lethal (Beall et al, 1962). Intradermal injections of PA + EF (or oedema toxin, ET) induce oedema in the skin (Stanley and Smith, 1961), and may also be lethal.…”
Section: The Molecular Characterization Of Lethal and Oedema Toxin Efmentioning
confidence: 99%
“…Alternatively, LT may cripple MDDC activity without overt cytotoxicity (Kassam et al, 2005;Tournier et al, 2005). LT contributes significantly to virulence and injection of purified LT induces shock and death in animals (Beall et al, 1962;Pezard et al, 1991). As a result, LT has received more attention than OT experimentally.…”
Section: Introductionmentioning
confidence: 99%